WORD OF MOUTH AND QUALITY SERVICES; THEIR IMPACT ON DESTINATION TRUST AND REVISIT INTENTION ON IN THE RIAU ISLANDS’ DESTINATION - Rizni Aulia Qadri (Management Department, Faculty of Economics and Business, Universitas Jambi, 2022)
This study aims to analyze whether word-of-mouth promotion and service quality have an impact on destination trust and intention to revisit tourism destinations in the Riau Archipelago. The population in this study were all tourists visiting the Riau Islands, both foreign and domestic tourists. Methodology: The sample is determined proportionally by considering the number of foreign and domestic tourists. The research sample was 350 tourists consisting of 150 foreign tourists and 200 domestic tourists. For analysis of data using with SmartPLS technique. Results: The results showed that all research hypotheses were accepted. This means that word of mouth and service quality has an impact on destination trust and revisit intention on Riau Islands’ destination.